Dielectric, mechanical and thermal properties of ZrO2–TiO2 materials obtained by microwave sintering at low temperature. Issue 19 (1st October 2021) - Guillén, René M.; Benavente, Rut; Salvador, María D.; Peñaranda, Felipe L.; Recio, Paloma; Moreno, Rodrigo; Borrell, Amparo
Abstract: The sinterability of 3Y-TZP/TiO2 materials using micrometre-sized ZrO2 and nanometre-sized TiO2 (16 wt%) by one-step fast microwave sintering at low temperature (1200–1300 °C) was investigated. Firstly, in situ detailed analysis of the dielectric properties of the material with temperature was carried out in order to measure the capacity of the material to transform microwave energy into heat. Another related parameter associated to microwave sintering is the penetration depth of the microwave radiation into the material, which showed great homogeneity from 400 °C. Secondly, the effect of sintering conditions on microstructure, density, hardness and coefficient of thermal expansion was evaluated. The X-ray diffraction study and microstructural characterization demonstrate that it is possible to obtain fully dense pieces (>99%) by microwave sintering, a condition yielding to a coarse-grained (~1–2 μm), quite hard (~13.7 GPa) 3Y-TZP/TiO2 material. However, the most important feature is the significant reduction of the thermal expansion coefficient (8·10 −6  K −1 ) as compared to that of 3Y-TZP. In addition, the results from conventional sintering at 1400–1500 °C with 2 and 6 h of dwell time are examined and compared. The materials obtained at 1500 °C showed high density with grain size and hardness similar to those obtained by microwave but with a dramatic difference in the power consumption of the sintering cycle, since the materials obtained by microwave used a maximum absorbed power of 120 W and a heating cycle of only 40 min.